\newfam\rsfs \newfam\bbold \def\scr#1{{\fam\rsfs #1}} \def\bb#1{{\fam\bbold #1}} \let\oldcal\cal \def\cal#1{{\oldcal #1}} \font\rsfsten=rsfs10 \font\rsfssev=rsfs7 \font\rsfsfiv=rsfs5 \textfont\rsfs=\rsfsten \scriptfont\rsfs=\rsfssev \scriptscriptfont\rsfs=\rsfsfiv \font\bbten=msbm10 \font\bbsev=msbm7 \font\bbfiv=msbm5 \textfont\bbold=\bbten \scriptfont\bbold=\bbsev \scriptscriptfont\bbold=\bbfiv \def\Pr{\bb P} \def\E{\bb E} \newcount\qnum \def\q{\afterassignment\qq\qnum=} \def\qq{\qqq{\number\qnum}} \def\qqq#1{\bigskip\goodbreak\noindent{\bf#1)}\smallskip} \def\align#1{\vcenter{\halign{$\displaystyle##\hfil$\tabskip1em&& $\hfil\displaystyle##$\cr#1}}} \def\fr#1#2{{#1\over #2}} \def\var{\mathop{\rm var}\nolimits} \def\cov{\mathop{\rm cov}\nolimits} \def\infint{\int_{-\infty}^\infty} \def\pa#1#2{\partial#1/\partial#2} \q1 (a) $$\Pr(|Z_n-a|>\epsilon) = \Pr(Z_n0.$ (b) $$\Pr(|\sqrt{Z_n}-\sqrt{a}|>\epsilon) = \Pr(\sqrt{Z_n}<\sqrt{a}-\epsilon) = \Pr(Z_n0$ as $n\to\infty,$ and limits to $1-e^{-x},$ by definition of the exponential. \q2 Let $Z_n$ be the normalization of sum $S_n$ of $n$ independent Bernoulli variables, each with parameter $p$ and thus mean $p$ and variance $pq.$ $$\Pr(|Z_n|\leq x) = \Pr(-x\leq Z_n\leq x) = \Pr(np-\sqrt{npq}x\leq S_n\leq np+\sqrt{npq}x) = \sum{n\choose k}p^k q^{n-k}.$$ By the central limit theorem, as $n\to\infty,$ $$\Pr(|Z_n|\leq x) = \Pr(Z_n\leq x) - \Pr(Z_n\leq -x) = \int_{-x}^x {1\over\sqrt{2\pi}}e^{-\fr12 u^2}du = 2\int_0^x {1\over\sqrt{2\pi}}e^{-\fr12 u^2}du.$$ \q3 $X_n,$ the binomial distribution is equivalent to the sum of $n$ independent Bernoulli distributions $B_i$ with parameter $p.$ $$\E([n^{-1}X_n-p]^2) = \E(n^{-2}[(B_1-p)+(B_2-p)+\cdots+(B_n-p)]^2) = n^{-2}(n\var(B_i)) = p(1-p)/n,$$ which $\to 0$, as $n\to\infty.$ Converging in mean square implies converging in probability, therefore the distribution converges in probability to $p.$ \q5 With $P_n$ the poisson distribution with parameter $n,$ $$\Pr(P_n = k) = {n^k e^{-\lambda}\over k!},$$ $$e^{-n}\left(1+n+{n^2\over 2!}+\cdots+{n^n\over n!}\right) = \sum_{k=0}^n \Pr(P_n=k) = \Pr(P_n\leq n).$$ $P_n = X_1+X_2+\cdots+X_n$ where $X_i$ has the Poisson distribution with parameter 1. The normalized version of $P_n$ is $(P_n-n)/\sqrt{x},$ because the mean and variance of $X_i$ is $1.$ As $n\to\infty,$ this distribution approaches the standard normal (by the central limit theorem), and $\Pr(P_n\leq n) \to \Pr(N(0,1)\leq0) = 1/2.$ \q7 $$\E([X_n+Y_n-(X+Y)]^2) = \E([X_n-X]^2) + \E([Y_n-Y]^2) + 2\E([Y_n-Y][X_n-X]).$$ As $n\to\infty,$ this approaches $2\E([Y_n-Y][X_n-x]) \leq 2\sqrt{\var(Y_n-Y)\var(X_n-X)},$ of which both variances $\to 0$ because $Y_n \to Y$ in mean square and similar for $X_n,$ and therefore the first expectation approaches zero and $X_n+Y_n \to X+Y.$ \q8 $$\E([X_n-X]^2)\to0\qquad\hbox{\it\ as } n\to\infty$$ Let $V=1.$ By Cauchy-Schwartz, $$\E(X_n-X)^2\leq\E([X_n-X]^2)\Rightarrow\E([X_n-X])\to 0,$$ as $n\to\infty.$ By linearity of expectations, $$\E(X_n)\to\E(X)\qquad\hbox{\it\ as } n\to\infty.$$ If $\Pr(Z_n=0) = 1-{1\over n}$ and $\Pr(Z_n=n) = {1\over n},$ $X_n\to X=0$ in probability because as $n\to\infty,$ $\Pr(X>\epsilon) \to 0,$ but $\E(X) = \E(0) = 0$ and $\E(X_n) = {n\over n} = 1.$ \q11 $$\Pr(|X|\geq a) = \Pr(g(X)\geq g(a)),$$ by the fact that $g$ is symmetric and strictly increasing on $x>0.$ $$\Pr(g(X)\geq g(a)) \leq {\E(g(X))\over g(a)},$$ by Markov's inequality (since $g(X)$ is a random variable) given that $g(x)>0,$ therefore the inequality is true. \q14 $X_n$ converges in mean square to the random variable $X,$ so $$\E([X_n-X]^2) \to 0\qquad\hbox{\it\ as } n\to\infty,$$ $$\E([X_n-X_m]^2) = \E([X_n-X-(X_m-X)]^2) = \E([X_n-X]^2)-2\E([X_n-X][X_m-X])+\E([X_m-X]^2) = 2\E([X_n-X][X_m-X]),$$ as $n,m\to\infty,$ from the first assumption. By the Cauchy-Schwartz inequality, $$\E([X_n-X][X_m-X])^2\leq \E([X_n-X]^2)\E([X_m-X])^2 \to 0,$$ as $n\to\infty,$ so $\E([X_n-X][X_m-X]) \to 0,$ so the assumption is proved. $$\cov(X_n,X_m) = \E([X_n-\E(X_n)][X_m-\E(X_m)]) = \E([X_n-\mu][X_m-\mu])$$ $X_n$ and $X_m$ are sufficiently similar to $X,$ so $$\E([X_n-\mu][X_m-\mu]) \to \E([X-\mu]^2) = \sigma^2 = \sqrt{\var(X_n)\var(X_m)} \Rightarrow \rho\to 1.$$ % An incomplete answer: how is it sufficiently similar? \bye